Question
upstudy study bank question image url

\( \left. \begin{array} { l } { 11 , y = - \frac { 5 } { 3 } x + 3 } \\ { y = \frac { 1 } { 3 } x - 3 } \end{array} \right. \)

Ask by Campbell Rodriguez. in the United States
Feb 25,2025

Upstudy AI Solution

Tutor-Verified Answer

Answer

The solution to the system of equations is \( (3, -2) \).

Solution

Solve the system of equations by following steps: - step0: Solve using the substitution method: \(\left\{ \begin{array}{l}-\frac{5}{3}x+3=y\\\frac{1}{3}x-3=y\end{array}\right.\) - step1: Rewrite the expression: \(\left\{ \begin{array}{l}y=-\frac{5}{3}x+3\\\frac{1}{3}x-3=y\end{array}\right.\) - step2: Substitute the value of \(y:\) \(\frac{1}{3}x-3=-\frac{5}{3}x+3\) - step3: Multiply both sides of the equation by LCM: \(\left(\frac{1}{3}x-3\right)\times 3=\left(-\frac{5}{3}x+3\right)\times 3\) - step4: Calculate: \(x-9=\left(-\frac{5}{3}x+3\right)\times 3\) - step5: Calculate: \(x-9=-5x+9\) - step6: Move the expression to the left side: \(x+5x=9+9\) - step7: Add and subtract: \(6x=9+9\) - step8: Add and subtract: \(6x=18\) - step9: Divide both sides: \(\frac{6x}{6}=\frac{18}{6}\) - step10: Divide the numbers: \(x=3\) - step11: Substitute the value of \(x:\) \(y=-\frac{5}{3}\times 3+3\) - step12: Calculate: \(y=-2\) - step13: Calculate: \(\left\{ \begin{array}{l}x=3\\y=-2\end{array}\right.\) - step14: Check the solution: \(\left\{ \begin{array}{l}x=3\\y=-2\end{array}\right.\) - step15: Rewrite: \(\left(x,y\right) = \left(3,-2\right)\) To solve the system of equations given by: 1. \( y = -\frac{5}{3}x + 3 \) 2. \( y = \frac{1}{3}x - 3 \) we can set the two equations equal to each other since they both equal \( y \): \[ -\frac{5}{3}x + 3 = \frac{1}{3}x - 3 \] Now, let's solve for \( x \): 1. First, add \(\frac{5}{3}x\) to both sides: \[ 3 = \frac{1}{3}x + \frac{5}{3}x - 3 \] 2. Combine the \( x \) terms: \[ 3 = \left(\frac{1}{3} + \frac{5}{3}\right)x - 3 \] \[ 3 = \frac{6}{3}x - 3 \] 3. Add 3 to both sides: \[ 3 + 3 = 2x \] \[ 6 = 2x \] 4. Divide both sides by 2: \[ x = 3 \] Now that we have \( x \), we can substitute it back into either equation to find \( y \). Let's use the second equation: \[ y = \frac{1}{3}(3) - 3 \] \[ y = 1 - 3 \] \[ y = -2 \] Thus, the solution to the system of equations is: \[ (x, y) = (3, -2) \]

Answered by UpStudy AI and reviewed by a Professional Tutor

error msg
Explain
Simplify this solution

Bonus Knowledge

Let's get excited about the lines and where they intersect! The equations you've provided represent two lines in a coordinate plane. By substituting \(x = 11\) into both equations, you can find the corresponding y-values. For the first equation, simply plug in \(x = 11\) to find \(y = -\frac{5}{3}(11) + 3\). Meanwhile, for the second equation, it’s just as easy with \(y = \frac{1}{3}(11) - 3\). Solving both will show where they meet! Now, if you want to determine where these two lines actually intersect, you can set \(-\frac{5}{3}x + 3 = \frac{1}{3}x - 3\) and solve for \(x\). That will lead you to the x-coordinate of their intersection point. After that, you'll plug that value back into either original equation to find the y-coordinate. It's all about finding that cool point where they shake hands! Happy graphing!

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy